Genetic Transformation System for Woody Plant Tripterygium wilfordii and Its Application to Product Natural Celastrol - Zhao, Yujun; Zhang, Yifeng; Su, Ping; Yang, Jian; Huang, Luqi; Gao, Wei (Frontiers in Plant Science, 2018)
Tripterygium wilfordii is a perennial woody liana medicinal plant with several crucial biological activities. Although studies on tissue culture have previously been conducted, research on genetic transformation is much more challenging and therefore results in slower progress. In the present study, a highly efficient transformation system involving the particle bombardment of T. wilfordii with the reporter egfp gene using the PDS-1000/He system was established. A total of seven parameters affecting the genetic transformation were investigated using an L18 (6×36)-type orthogonal array. The result indicated that DNA delivery conditions of 3-cm target distance, 1100 psi helium pressure, 28 mmHg chamber vacuum pressure, 3 times number of bombardment, CaCl2 as precipitation agent, 2 μg plasmid DNA concentration and 48 h post-bombardment incubation time were optimal for T. wilfordii cell suspensions transformation. The average transformation efficiency was 19.17%. Based on this transformation system, the overexpression of two T. wilfordii farnesyl pyrophosphate synthases (TwFPSs) was performed in cell suspensions. Integration of the TwFPSs in the genome was verified by PCR analysis and also by Southern blotting using hygromycin gene as a probe. Real-time quantitative PCR analysis showed that the expression of TwFPS1&2 was highly up regulated in transgenic cell suspensions compared with control cells. The detection of metabolites showed that TwFPS1&2 could highly increase the celastrol content (973.60 μg/g) in transgenic cells. These results indicated that this transformation system is an effective protocol for characterizing the function of genes in the terpenoid biosynthetic pathway.